A qualitative study of patient experiences of decentralized acute healthcare services - Ann-Chatrin Linqvist Leonardsen; Lilliana Del Busso; Vigdis Abrahamsen Grøndahl; Waleed Ghanima; Paul Barach; Lars-Petter Jelsness-Jørgensen (Scandinavian Journal of Primary Health Care, 2016)
Objective: Municipality acute wards (MAWs) have recently been launched in Norway as an alternative to hospitalizations, and are aimed at providing treatment for patients who otherwise would have been hospitalized. The objective of this study was to explore how patients normally admitted to hospitals perceived the quality and safety of treatment in MAWs. Design: The study had a qualitative design. Thematic analysis was used to analyze the data. Setting: The study was conducted in a county in south-eastern Norway and included five different MAWs. Patients: Semi-structured interviews were conducted with 27 participants who had required acute health care and who had been discharged from the five MAWs. Results: Three subthemes were identified that related to the overarching theme of hospital-like standards (“almost a hospital, but…”), namely (a) treatment and competence, (b) location and physical environment, and (c) adequate time for care. Participants reported the treatment to be comparable to hospital care, but they also experienced limitations. Participants spoke positively about MAW personnel and the advantages of having a single patient room, a calm environment, and proximity to home. Conclusions: Participants felt safe when treated at MAWs, even though they realized that the diagnostic services were not similar to that in hospitals. Geographical proximity, treatment facilities and time for care positively distinguished MAWs from hospitals, while the lack of diagnostic resources was stressed as a limitation.Key points   Municipality acute wards (MAWs) have been implemented across Norway. Research on patient perspectives on the decentralization of acute healthcare in MAWs is lacking.   • Patients perceive decentralized acute healthcare and treatment as being comparable to the quality they would have expected in hospitals.   • Geographical proximity, a home-like atmosphere and time for care were aspects stressed as positive features of the decentralized services.   • Lack of diagnostic resources was seen as a limitation.